Cell Phoney - Julia Cook (National Center for Youth Issues, 2015)
Grades 2-8) After much anticipation, Joanie Maloney finally gets her very own cell phone! Knowing that owning a cell phone requires responsibility and sound judgment, Joanie's mom requires her to complete a Cell Phone Safety Course. (3z(BMom, it's a phone... it's not a weapon!(3y (BJoanie exclaims.Along with Joanie, children will learn the six rules of cell phone usage which are designed not only to keep them safe, but also to keep them from being tempted to hurt others. By knowing the rules, children can become masters of their cell phones and avoid becoming a (3z(BCell Phoney!(3y (BPaperback, 32 pages.s
Keywords: How We Organize Ourselves -- -DIgital Media